Bevacizumab has differential and dose-dependent effects on glioma blood vessels and tumor cells - Baumgarten, Louisa von; Brucker, David; Tirniceru, Anca; Kienast, Yvonne; Grau, Stefan; Burgold, Steffen; Herms, Jochen; Winkler, Frank (Clinical cancer research, 2011)
Purpose: Bevacizumab targets VEGF-A and has proved beneficial in glioma patients, improving clinical symptoms by the reduction of tumor edema. However, it remains controversial whether or not bevacizumab exerts antitumor effects in addition to (and potentially independent of) its effects on tumor vessels, and it is unknown what doses are needed to achieve this.Experimental Design: We established a novel orthotopic glioma mouse model that allowed us to simultaneously study the kinetics of the morphologic and functional vascular changes, tumor growth, and the viability of individual tumor cells during the course of anti-VEGF therapy in the same microscopic tumor region in real-time. Three doses of bevacizumab were compared, a subclinical dose and two clinical doses (medium and high).Results: Low (subclinical) doses of bevacizumab led to a significant reduction of the total vascular volume without affecting tumor cell viability or the overall tumor growth rates. Medium and high doses triggered a similar degree of vascular regression but significantly decreased tumor growth and prolonged survival. Remaining vessels revealed morphologic features of vascular normalization, reduced permeability, and an increase in blood flow velocity; the latter was dose dependent. We observed an uncoupling of the antitumoral and the antivascular effects of bevacizumab with the high dose only, which showed the potential to cause microregional glioma cell regression. In some tumor regions, pronounced glioma cell regression occurred even without vascular regression. In vitro, there was no effect of bevacizumab on glioma cell proliferation.Conclusions: Regression of glioma cells can occur independently from vascular regression, suggesting that high doses of bevacizumab have indirect anticancer cell properties in vivo. Clin Cancer Res; 17(19); 6192-205. ©2011 AACR.
Gesehen am 19.12.2022